Electrochemical deposition of copper decorated titania nanotubes and its visible light photocatalytic performance - Lim, Y.C; Siti, A.S.; Nur Amiera, P.; Kanakaraju, Devagi; Lim, Y.P. (American Institute of Physics Inc., 2017)
Coupling of titania with narrow band gap materials has been a promising strategy in preparing visible light responsive photocatalyst. In this work, self-organized copper decorated TiO2 nanotube (Cu/TNT) was prepared via electrodeposition of Cu onto highly ordered titania nanotube arrays (TNT). The catalysts were characterized by X-ray diffraction, diffuse reflectance spectroscopy (DRS), field emission scanning electron microscopy (FESEM) and energy-dispersive X-ray spectroscopy (EDX). The DRS studies clearly show the extended absorption of Cu/TNT into the visible region and present a red shift of band gap to 2.1 eV. FESEM analysis has shown the dispersion of cubic-like Cu particles upon electrodeposition and EDX analysis supports the presence of copper species on the nanotubes surface. The photocatalytic ability of Cu/TNT was evaluated by the degradation of methyl orange from aqueous solution under low power visible light illumination. Compared to TNT, an appreciable improvement in methyl orange removal was observed for Cu/TNT and the highest removal efficiency of 80% was achieved. The effects of catalyst loading and samples repeatability were investigated and under optimum conditions, the removal efficiency of methyl orange over Cu/TNT had further increased to 93.4%. This work has demonstrated a feasible and simple way to introduce narrow band gap transition metal into nanotube arrays, which could create novel properties for functionalized nanotube arrays as well as promise a wide range of applications.